Perancangan Desain UI/UX Aplikasi Penjualan Buku Pada CV.Shabilul Haq Offset - Asnini Laisani; M. Soekarno Putra (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
Abstract in order to increase revenue, many companies increase the use of information systems. Aside from being a sales medium, the use of information systems is also a place to attract sales promotions to potential customers. Problems that occur in CV. Sabilul Haq as a book seller, still doesn't have a system that can carry out book sales transaction, therefore we need a system design that has an attractive appearance so that it can attract potential customers, such as using UI/UX to produce a system that has a dynamic and attractive appearance. customer interest. Because the first thing customers see is the appearance, the more attractive it is, the more it makes customers interested in shopping at the store. The results of this study is an application design that can conduct book sales transactions on CV. Sabilul Haq and has an attractive display design with UI/UX. Keywords— Application, Book, Sale, UI/UX